ECONOMIC AND STATISTICAL ANALYSIS OF REGIONAL TRENDS IN THE DEVELOPMENT OF AGRICULTURE IN THE CONTEXT OF THE TERRITORY OF THE REGION - Aysachev Abdulfotix Abdulfaizovich (Web of Journals Publishing, 2024)
The article describes the trends in the development of regional agriculture in the Andijan region in 2010-2019 based on economic and statistical analysis of the main indicators. On the basis of the identified trends of the changes of the territory, determined the directions of agricultural development of regional branch.
Keywords: economic and statistical analysis, gross regional product, gross regional agricultural output, absolute growth, relative growth, regional and territorial analysis, dehkan farms, farms, trends.